0044 White house campus sexual assault task force update. (26th April 2015) - Fox, Kate; Fowler, Dawn
Abstract : Statement of purpose: Sexual Violence is a significant problem in the United States. Nearly 1 in 5 women (19.3%) and 1 in 59 men (1.7%) in the United States have been raped at some time in their lives. In a study of undergraduate women, 19% experienced attempted or completed sexual assault since entering college. As part of the White House initiative to prevent campus sexual assault, CDC will convene a panel of experts (e.g., sexual violence prevention practitioners and college and university staff and leadership) in early 2015 to identify emerging, promising practices to prevent sexual assault on campus and make recommendations. Methods/Approach: CDC will share updates on activities related to the White House Campus Sexual Assault Task Force, highlight CDC's work to prevent campus sexual assault, and offer experiences from states and universities working on this issue. The CDC presenters will cover the background, epidemiology, potential interventions, and tools and resources to support rape prevention on campus. Partners (sexual violence prevention practitioners or university partners) will discuss efforts implemented at universities and future directions for campus sexual assault prevention. The session will include time for discussion with panellists/presenters to hear more about experiences and efforts by universities and CDC. Results: Session attendees will learn about emerging, promising practices to prevent sexual assault on campuses and how those can be incorporated into their violence prevention programs. Conclusions: Emerging strategies can be used to address the issue of campus sexual assault. By understanding the best available evidence, universities and other partners can collaborate to prevent sexual assault. Significance and contribution to the field: Universities and their partners across the country are working to address and prevent campus sexual assault. This presentation will provide information on the best available evidence regarding strategies and practices to prevent sexual assault and help the broader injury prevention audience better understand the issue and potential steps to address it.